2011
DOI: 10.14778/2095686.2095688
|View full text |Cite
|
Sign up to set email alerts
|

B+-tree index optimization by exploiting internal parallelism of flash-based solid state drives

Abstract: Previous research addressed the potential problems of the harddisk oriented design of DBMSs of flashSSDs. In this paper, we focus on exploiting potential benefits of flashSSDs. First, we examine the internal parallelism issues of flashSSDs by conducting benchmarks to various flashSSDs. Then, we suggest algorithm-design principles in order to best benefit from the internal parallelism. We present a new I/O request concept, called psync I/O that can exploit the internal parallelism of flashSSDs in a single proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Typically, the data transfers from/to the multiple packages on the same channel get serialized. However, data transfers can be interleaved with other operations (e.g., reading data from a page to the data register) on other packages sharing the same channel [10,29]. This interleaving provides package-level parallelism.…”
Section: Parallelism In Ssd Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the data transfers from/to the multiple packages on the same channel get serialized. However, data transfers can be interleaved with other operations (e.g., reading data from a page to the data register) on other packages sharing the same channel [10,29]. This interleaving provides package-level parallelism.…”
Section: Parallelism In Ssd Architecturementioning
confidence: 99%
“…However, as we will show later, this design pattern aids in instrumenting patterns 1-4. Plane-level parallelism: Earlier works [18,29] have shown that intermingling small reads and small writes affects plane-level parallelism, leading to a performance drop of up to 1.3X in throughput compared to issuing consecutive small reads followed by consecutive small writes. However, the above design patterns already dictate that we issue large writes (DP2) and small reads (small page reads for lookup requests; DP1), which already ensure that small reads and small writes are not intermingled by default.…”
Section: Extracting Parallelismmentioning
confidence: 99%
“…Chen et al [2] studied on how to uncover internal parallelism features of SSDs and revealed that exploiting internal parallelism can significantly improve I/O performance. In the study of [6], researchers focused on finding an efficient way to generate parallel I/Os to access SSDs. By assessing different methods to create parallel I/O, authors suggest a new I/O request method and design a new B+-tree variant called PIO B-tree to exploit internal parallelism of SSDs.…”
Section: Related Workmentioning
confidence: 99%
“…With the rapid development of flash memory and solid state drives (SSDs), optimizing B+-tree for flash memory has attracted many researchers in recent years [1][2][3][4]. Implementing B+-tree on SSD can get better read performance because of the fast read speed of flash memory, but the writing operations caused by B+-tree will worsen the overall time performance, due to the poor random write speed of flash memory.…”
Section: Introductionmentioning
confidence: 99%
“…The pages inside huge leaf nodes are stored on HDD or SSD according to the states of these pages, while the interior nodes are stored on SSD. (3) We conduct experiments on a real hybrid storage system consisting of one HDD, a low-end SSD, and a high-end SSD. The results show that the HybridB tree is superior to both the B+-tree on HDD and the B+-tree on SSD/HDD, in terms of time performance, SSD write count, and buffer costs.…”
Section: Introductionmentioning
confidence: 99%